A historical argument for proportionality under the Indian Constitution. Issue 1 (2nd January 2018) - Narayan, Vikram Aditya; Sindhu, Jahnavi
ABSTRACT: The Indian Constitution does not stipulate a general standard for judicial review of state action. The Supreme Court has developed separate standards of review under the various fundamental rights provisions. Much ink has been spilt on deriving the standard from ascertaining the precise meaning of constitutional phrases such as "reasonable ", "procedure established by law", "equal protection". Scholars have pointed out that most of the standards developed by the judiciary are deferential to the state's evaluation of how fundamental rights may be restricted. Based on a historical, textual and structural reading of the Constitution, this paper argues that the Framers of the Indian Constitution intended for the judiciary to come up with stricter standards of judicial review. We argue that the Framers evolved a culture of justification through the Indian Constitution, and that the proportionality test best serves the objectives underlying the Constitution.